Detection of genital chlamydial and gonococcal infection using urine samples: A community-based study from India. Issue 1 (January 2018) - Krishnan, Anjana; Sabeena, Sasidharanpillai; Bhat, Parvati V.; Kamath, Veena; Hindol, Maity; Zadeh, Vahid R.; Arunkumar, Govindakarnavar
Abstract: Sexually transmitted infections (STI) have a major impact on the reproductive health of women. Among the different etiological agents of STIs, Chlamydia trachomatis and Neisseria gonorrhoeae are the main bacterial pathogens that cause sexually transmitted infections in women. The aim of the study was to estimate the prevalence of genital chlamydial and gonococcal infection among women in the age group of 18–65 years from a community-based setting. A community-based cross-sectional study was performed using the archived urine samples (n = 811) of women in the age group of 18–65 years for C. trachomatis and N. gonorrhoeae using a multiplex conventional Polymerase Chain Reaction (PCR). Out of 811 samples tested in the present study, 2 (0.24%) were tested positive for C. trachomatis and none were positive for N. gonorrhoeae . The study demonstrates the very low prevalence of C. trachomatis and N. gonorrhoeae infection in a rural community. For large population-based screening, urine samples were observed to be more socially acceptable and cost-effective.